Design of a sequential control circuit for an Industrial Robot using cascading method - Arul Raj, K.; Malayappan, S.; Sathya Arunachalam, S.; Venugopal, S.; Ramalingam, D. (Universiti Malaysia Perlis, 2009)
Organized by School of Mechatronic Engineering (UniMAP) & co-organized by The Institution of Engineering Malaysia (IEM), 11th - 13th October 2009 at Batu Feringhi, Penang, Malaysia.